Describing the Summary of Single Site Extreme Wave Analysis in the Pacific Ocean Comparing Stationary and Non-Stationary GEV Models - F. Calderón-Vega; C. Mosso; A. D. Garcia-Soto; E. Delgadillo-Ruiz (New Ideas Concerning Science and Technology Vol. 4, 2021)
An extreme value analysis of maximum significant waves recorded at a buoy located in the Pacific Ocean is summarized from a previous study in this book chapter. The analysis was carried out from two perspectives, by considering a Generalized Extreme Value (GEV) model with stationary distribution (i.e., the time variations are not accounted for), and by considering a non-stationary GEV model, which incorporates the monthly seasonality of maximum observed values in time increments; the maximum significant wave behavior was parameterized using harmonic functions for the distribution measures. Both approaches were compared for a single buoy. In the study a seasonality effect was found, which was also present at the Gulf of Mexico in previous studies, and which cannot be captured by a stationary model. Future studies for more buoys and wider regions are desirable, to characterized extreme wave activity, aimed at improving the design and management of coasts and ports by including seasonality.